2009
DOI: 10.1038/jid.2008.453
|View full text |Cite
|
Sign up to set email alerts
|

High Ro52 Expression in Spontaneous and UV-Induced Cutaneous Inflammation

Abstract: Ro52 is an E3 ubiquitin ligase with a recently identified regulatory role in inflammation. The protein is targeted by autoantibodies in rheumatic diseases, and Ro52 autoantibodies are specifically associated with cutaneous lupus erythematosus (CLE) and photosensitivity. The aim of this study was to investigate cutaneous Ro52 expression in CLE patients and to examine whether UVR might modulate Ro52. Ro52 expression was assessed by immunohistochemistry in biopsies derived from CLE lesions (n=25), nonlesional (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 32 publications
2
39
1
1
Order By: Relevance
“…Spontaneous SLE has been linked to alterations in expression (57) and activation of TLR7/9 (17, 18), dysregulation of the cytosolic sensors p202 and AIM2 (24,25), and polymorphisms (21) and heightened expression in TRIM21 (22). We now define that defective degradation of FcγR-bound cargo in the lysosome is a critical upstream event that overburdens the phagolysosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous SLE has been linked to alterations in expression (57) and activation of TLR7/9 (17, 18), dysregulation of the cytosolic sensors p202 and AIM2 (24,25), and polymorphisms (21) and heightened expression in TRIM21 (22). We now define that defective degradation of FcγR-bound cargo in the lysosome is a critical upstream event that overburdens the phagolysosome.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the sensor that recognizes cytoplasmic IgG (tripartite motif containing 21; TRIM21; ref. 21), and heightened expression of TRIM21 (22) and its regulated genes (22,23), have been identified in SLE patients. Further, two cytosolic sensors that recognize dsDNA (p202 and absent in melanoma 2; AIM2) have been implicated in type 1 interferon (IFN) production in murine lupus (24,25).…”
mentioning
confidence: 99%
“…A large number of TRIM genes are induced by type I or type II IFNs (e.g., during viral or bacterial infections) (20,21). Interestingly, some TRIM genes are also overexpressed in systemic autoimmune diseases such as systemic lupus erythematosus and Sjögren's syndrome, suggesting that TRIM proteins participate in the pathogenesis of these diseases (22)(23)(24). Trim21 is induced by both type I and type II IFNs and is overexpressed in patients with systemic lupus erythematosus and Sjögren's syndrome compared with healthy controls (23,24).…”
Section: /2mentioning
confidence: 99%
“…Interestingly, some TRIM genes are also overexpressed in systemic autoimmune diseases such as systemic lupus erythematosus and Sjögren's syndrome, suggesting that TRIM proteins participate in the pathogenesis of these diseases (22)(23)(24). Trim21 is induced by both type I and type II IFNs and is overexpressed in patients with systemic lupus erythematosus and Sjögren's syndrome compared with healthy controls (23,24). The molecular mechanisms regulating Trim21 expression are unknown, but because Trim21 is induced by IFNs we hypothesized that transcription factors activated by IFN signaling control Trim21 expression.…”
Section: /2mentioning
confidence: 99%
“…24 Meanwhile this testing regimen has received much attention because phototesting is not only an optimal way to evaluate photosensitivity in patients with CLE, but the reproducibility of inducing skin lesions by UVA and UVB irradiation makes it an ideal model for several experimental approaches, which allow the study of inflammatory and immunologic events that take place before and during lesion formation. [25][26][27][28] Most interestingly, the phototesting studies showed that the development of skin lesions in patients with CLE is characterized by a latency period for up to 3 weeks in contrast to other photodermatoses, such as polymorphous light eruption (PLE). 24 Therefore, most patients with CLE are not aware of the link between sun exposure and their disease and deny any effect of UV irradiation on the induction or outcome of their cutaneous lesions.…”
mentioning
confidence: 99%